Macronyssus crosbyi - Orlova, Maria V.; Anisimov, Nikolay V. (Zenodo, 2023)
Macronyssus crosbyi (Ewing & Stover, 1915) Distribution – Holarctic (Radovsky 1967; Stanyukovich 1997). Hosts (in the Old World) – Myotis dasycneme , My. brandtii , and My. daubentonii (Stanyukovich 1990), M. sibiricus (Orlova et al. 2017a), Plecotus auritus (Stanyukovich 1990), P. ognevi (as Plecotus auritus – Medvedev et al. 1991), Pipistrellus nathusii , Vespertilio murinus and Eptesicus nylssonii (Stanyukovich 1990). Published as part of Orlova, Maria V. & Anisimov, Nikolay V., 2023, Three new species of bat-parasitic gamasid mites of the genera Spinturnix, Macronyssus and Steatonyssus (Acari: Mesostigmata: Spinturnicidae, Macronyssidae) from Siberia and Mongolia, with keys to species of Russia and adjacent countries, pp. 211-239 in Persian Journal of Acarology 12 (2) on page 224, DOI:10.22073/pja.v12i2.76740, http://zenodo.org/record/8113590